Determination of coeluted isomers in wine samples by application of MS/MS deconvolution analysis. (17th July 2020) - Menicatti, Marta; Pallecchi, Marco; Ricciutelli, Massimo; Galarini, Roberta; Moretti, Simone; Sagratini, Gianni; Vittori, Sauro; Lucarini, Simone; Caprioli, Giovanni; Bartolucci, Gianluca
Abstract: Two organic acids isomers, 3‐isopropylmalic acid (3‐IPMA) and 2‐isopropylmalic acid (2‐IPMA), were identified and quantified in wine samples by using an LC–MS/MS method without any chromatographic separation, but processing the MS/MS data with a recently developed deconvolution algorithm (LEDA: linear equations deconvolution analysis), thus decreasing the time necessary for the process. In particular, the LEDA tool processes the MS/MS signals and assigns the relative concentrations (abundances) of the isomers in the sample, at the mg L −1 level. The efficiency of MS/MS signal assignment was improved by introducing five linear equations to define the LEDA matrix. Then, as a novel approach, an overdetermined system of linear equations was applied for the deconvolution of isomers. The use of LEDA to identify and quantify the isomers in wine samples, together with the choice of a short LC column and a fast elution gradient, simplifies the process and shortens the time needed. Furthermore, it was evaluated the quantitative determination of the IPMA isomers by using the calibration curve provided by the precursor ion MRM transition data. The calculated values of accuracy (recovery between 82.6% and 99.8%) and precision (RSD between 0.4% and 4.0%) confirm the validity of this quantitative approach and the ability of LEDA to establish the correct percentage of the MS/MS signal for each isomer. Finally, to compare the conventional LC–MS/MS method and our proposed method of LC–MS/MS coupled with LEDA post‐processing elaboration, a series of real wine samples were analysed by both methods, and the results were compared.